Object-oriented and ontology context-aware modeling based on XML - Xu Jianfeng; Wang Dong (2012 2nd International Conference on Computer Science and Network Technology, 2012)
In order to solve the problem of providing service to users by using context-aware modeling in pervasive computing, this paper proposes a context-aware modeling method named of object-oriented and ontology modeling based on XML. Firstly, the most used type of context information is summarized and the difference between them is analyzed; secondly, the latest context-aware modeling technique is introduced, as well as their advantages and disadvantages, and then this paper proposes an improved model and software modeling framework; lastly, this improved model is verified by using different sizes of context data and compared with other context-aware modeling experiment, and the experiment result shows that this improved modeling method could provide excellent performance for model-building and query in context-aware system.